PERAN GURU PENDIDIKAN AGAMA ISLAM DALAM MENINGKATKAN MOTIVASI BELAJAR DAN KEMAMPUAN MEMBACA AL-QUR’AN SISWA DI MA YASTI KABUPATEN SUKABUMI - Ari Maulana Ibrahim; M Ikhsan Permana; Sherly Dwi Pratiwi; M Ali Nuryana (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the role of Islamic Religious Education teachers in improving students’ learning motivation and Qur’anic reading ability at MA Yasti, Sukabumi. This research employed a qualitative approach with a descriptive research design. This approach was chosen to gain an in-depth understanding of the role of Islamic Religious Education teachers in the learning process, as well as the factors influencing students’ learning motivation and Qur’anic reading skills. The research subjects consisted of the head of the madrasah, Islamic Religious Education teachers, homeroom teachers, and students selected through purposive sampling. Data were collected through interviews, observations, and documentation. Data analysis was carried out through data reduction, data presentation, and conclusion drawing, while data validity was ensured through source triangulation and method triangulation. The findings revealed that Islamic Religious Education teachers play significant roles as educators, motivators, facilitators, mentors, and evaluators in improving students’ learning motivation and Qur’anic reading ability. The teachers’ efforts included providing motivation, applying interactive learning methods, habituating students to read the Qur’an before class, guiding tajwid and makharij al-huruf, implementing the talaqqi method, and conducting periodic evaluations. The results also showed improvements in students’ learning participation, self-confidence, and Qur’anic reading proficiency. Supporting factors included teacher competence, a religious school environment, learning facilities, and parental support, while inhibiting factors included low motivation among some students, differences in basic abilities, and limited instructional time.